Police X Archives as a reaction of investigative practice to the statutory obligation to explain cases of murder committed until the statute of limitations expires - Sygit, Bogusław (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article indicates a significant role of the Police X Archives in the investigative practice of law enforcement authorities. The author emphasized the importance of those units, especially these in legal orders, in which the legislators introduce the institution of prosecution’s expiration. The author also mentioned the need of organizational changes in the currently functioning system, while presenting a number of demands that could improve the work of the undetected crime police team.